3D geospatial database from terrestrial /laser scanning (TLS) data - Abdul Rahman, Alias; Chen, Tet Khuan; Azri, Nor Suhaibah; Gurcan, Buyuksalih (2008)
Most major cities are being managed spatially by 2D geo-DBMS, however, unlike Istanbul city it is in the verge of 3D spatial database management system for thousands of its 3D objects (mainly buildings). The 3D database is one of the products generated from mapping and GIS initiatives currently being undertaken by the city municipality. This paper describes the development of 3D database with the leading geo-DBMS, i.e. Oracle Spatial 10g for the historical peninsula region in Istanbul, Turkey and the data are mainly captured via terrestrial laser scanned (TLS) datasets. Useful 3D geoinformation could be generated from such 3D database, thus an excellent tool for decision making for the city planning purposes as current GIS software faces some difficulties to perform such operations. The paper also highlights new 3D spatial operations developed for possible spatial analysis of 3D objects (surface and underground objects).